Primary adenocarcinoma of the appendix: a case report - Stanosz, Stanisław; Stanosz, Małgorzata; von Mach-Szczypiński, Jaroslaw (Contemporary Oncology/Współczesna Onkologia, 2007)
The aim of this work was to assess the dependence between concentration of histamine in serum and primary mammary gland cancer tissue and activity of histamine metabolism enzymes. The work concerned 95 women age 38-70, divided into two groups. Group I (control) consisted of 30 women with physiological mammary gland. Group II consisted of 65 women with ductal breast cancer. In both groups the authors evaluated histamine concentration in serum by immunoenzymatic method, the concentration of histamine in tissue and metabolic enzymes of histamine: histidine decarboxylase and aromatic L-amino acid decarboxylase, N- histamine methyltransferase, monoamine oxidase B and diamine oxidase. The 24 h expulsion of methyloimidazolooctan acid was evaluated with chromatography method. Statistical analysis was performed based on Statistica P Ed Statsoft Kraków 1998, Pearsona correlation factor p<0.05 The authors discovered a significant increase in concentration of histamine in serum p<0.01, in tissue of ductal breast cancer p<0.001, activity of histidine decarboxylase p<0.01, aromatic L-amino acid p<0.05, histamine methyltransferase p<0,05. Activity of monoamin oxidase B p<0.01, diamine oxidase p<0.001, showed a significant decrease in comparison to the control group. Conclusion: 1. High concentration of histamine in serum and tissue of ductal breast cancer could provoke increased release of histamine from cancer tissue. 2. Significant increase of histamine tissue of ductal breast cancer could promote this monoamine in pathological changes in cancer. 3. The expression of disorders in histamine metabolism in tissue of ductal breast cancer is a significant increase of histamine synthesis enzyme activity and decrease of biotransformation histamine enzymes. 4. The high concentration of histamine in serum in women with ductal breast cancer that could promote this monoamine in pathological changes in cancer is not dependent on tumour size but on level of malignancy and number of metastases.